2014
DOI: 10.1007/s12350-013-9817-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of high-resolution attenuation-corrected Anger-camera SPECT in the detection of coronary artery disease

Abstract: New Anger technology incorporating innovative improvements results in high image quality with excellent interpretive certainty and high diagnostic accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The switch from the standard, filtered back projection reconstruction method to iterative algorithms, which include depth independent resolution recovery, noise regularization, and scatter and attenuation correction, has improved the signalto-noise ratio and image quality. This also allows for low-dose imaging using a standard acquisition time with reduced radiation exposure to the patient and operator,without compromising image quality and accuracy in the detection of CAD [30][31][32]. This is consistent with the American Society of Nuclear Cardiology's goal to reduce the radiation dose to ≤9 mSv in 50% of MPI studies by 2014.…”
Section: Introductionsupporting
confidence: 72%
“…The switch from the standard, filtered back projection reconstruction method to iterative algorithms, which include depth independent resolution recovery, noise regularization, and scatter and attenuation correction, has improved the signalto-noise ratio and image quality. This also allows for low-dose imaging using a standard acquisition time with reduced radiation exposure to the patient and operator,without compromising image quality and accuracy in the detection of CAD [30][31][32]. This is consistent with the American Society of Nuclear Cardiology's goal to reduce the radiation dose to ≤9 mSv in 50% of MPI studies by 2014.…”
Section: Introductionsupporting
confidence: 72%
“…However, recent studies have demonstrated the potential superiority of 128 matrix with 3.2-mm pixel size when new reconstruction methods with resolution recovery are used on standard SPECT cameras. 55 For the CZT SPECT camera systems, the usual pixel size is 2.5 mm and 128 x 128 matrix size.…”
Section: Pixel and Matrix Sizementioning
confidence: 99%
“…4 Improvements in detection of left main disease have been demonstrated with attenuation corrected SPECT 5 and improvements in detection of multivessel CAD have recently been demonstrated using a high-resolution SPECT camera incorporating linesource attenuation correction, noise reduction, and resolution recovery algorithms. 6 Use of a newer generation CZT SPECT camera has also been shown to result in improved accuracy for detecting multi-vessel CAD. 7 …”
Section: Soft Tissue Attenuationmentioning
confidence: 99%